Efektifitas Konseling KBPP dengan Menggunakan Roda Klop dan Leaflet Terhadap Keberhasilan KB Pasca Persalinan di Puskesmas Kotabaru - Novi Sumiani; Nofa Anggraini (Universitas Malahayati Lampung, 2024)
ABSTRACT At the Kotabaru Health Center, out of 10 mothers giving birth in March 2023 who received counseling with a clop wheel and leaflets, there were 4 mothers who were willing to take part in postpartum family planning with the MKJP Implant Contraceptive type. (KB Kotabaru Health Center Register March, 2023). Based on this, above, the researcher is interested in conducting research entitled